Judicial Contra Legem Reasoning in the Division of Marital Joint Property: A Maqāṣid al-Sharī‘ah and Distributive Justice Perspective - Syam, Siti Arifah; Mhd. Syahnan; Lubis, Fauziah (JURNAL ILMIAH GEMA PERENCANA, 2025)
The distribution of marital joint property after divorce in Indonesian Islamic family law is normatively regulated by Article 97 of the Compilation of Islamic Law (KHI), which mandates an equal division (50:50) between spouses. However, the rigid application of this provision often fails to achieve substantive justice, as it disregards actual contributions, power relations within marriage, and structural gender inequalities. This study aims to examine the legitimacy of contra legem judicial decisions in marital property disputes and to reconstruct a more just model of distribution based on the perspective of maqāṣid al-sharī‘ah. This research employs a normative legal method using statutory, conceptual, and case-based approaches. The analysis is grounded in John Rawls’ theory of distributive justice as the grand theory, Satjipto Rahardjo’s progressive law as the middle theory, and Yasser Auda’s maqāṣid al-sharī‘ah framework as the applied theory. The findings demonstrate that the mechanical 50:50 division of joint property represents formal equality rather than substantive justice and, in certain cases, perpetuates injustice against the economically and socially disadvantaged spouse, particularly women. The study further finds that contra legem judicial rulings in joint property cases possess strong juridical, philosophical, and ethical justification when based on factual contributions and contextual realities. From a maqāṣid perspective, the distribution of marital property must prioritize justice (al-‘adl), protection of wealth (ḥifẓ al-māl), and public welfare (maṣlaḥah), rather than mere numerical equality.